Detection of extended-spectrum β-lactamase in Pseudomonas aeruginosa - Aggarwal Ritu; Chaudhary Uma; Bala Kiran (Wolters Kluwer Medknow Publications, 2008)
Purpose: The present study was designed to detect the extended-spectrum β-lactamase (ESBL) production in Pseudomonas aeruginosa and to evaluate the susceptibility pattern. Materials and Methods: One hundred forty-eight isolates of P. aeruginosa were analyzed for the presence of ESBL enzyme by double disc synergy test. Antibiotic sensitivity pattern of ESBL-positive P. aeruginosa was determined. Results: Of the 148 isolates tested, 30 (20.27%) were found to be positive. Maximum ESBL production was found in sputum and tracheostomy swabs (28.57%), followed by pus (24.13%), urine (19.04%), cerebrospinal fluid (CSF) and other sterile body fluids (15.38%) and blood (7.14%). All the ESBL-producing P. aeruginosa isolates were multi-drug-resistant. Isolates were 100% sensitive to imipenem. Ofloxacin was the second most (70%) effective drug. Conclusion: From this study, we conclude the presence of ESBL-positive P. aeruginosa in our hospital. This has important implications as carbapenems remain the only choice of treatment for infections caused by these organisms. The control measures include judicious use of antibiotics and implementation of appropriate infection control measures to control the spread of these strains in the hospital